Revisiting the Efficient Market Hypothesis: An Empirical Investigation of Indian Capital Markets (2001-2014) - Giridharan, K. S. (International Journal of Psychosocial Rehabilitation, 2015)
This study critically evaluates the weak-form efficiency of the Indian stock market from 2001 to 2014, deploying a focused analytical lens on the NSE’s NIFTY index along with six vital sectoral indices: Pharmaceuticals, Information Technology, Multinational Corporations, Banking, Fast-Moving Consumer Goods, and Nifty Junior. With a robust methodological framework, the investigation applies rigorous univariate time series analysis techniques to interrogate the indices’ return patterns. This includes advanced statistical tests such as run tests for detecting dependencies, unit root tests for assessing stationarity, and autocorrelation functions (ACF) coupled with correlograms for measuring the predictability of stock returns. The research fills a critical gap in literature by providing empirical insights into the market dynamics of an emerging economy. The evidence gathered points to significant anomalies that challenge the notion of weak-form efficiency in the Indian stock markets during the assessed period. The findings have substantial implications for investors, policymakers, and scholars, calling for reconsidering the prevalent investment strategies and regulatory frameworks.